The Canine Erythrocyte Sedimentation Rate (ESR): Evaluation of a Point-of-Care Testing Device (MINIPET DIESSE) - Militello, Carlo (Vet Med Int, 2020)
The erythrocyte sedimentation rate (ESR) in canine medicine has been replaced by the evaluation of a few sensitive markers of the acute-phase proteins. The aim of the study was to evaluate the ESR using a point-of-care (MINIPET, DIESSE Diagnostica Senese S.p.A.) device (ESR-MP) and to compare the results with the gold standard Westergren method (ESR-W) in dogs. One hundred and nineteen K3-EDTA blood samples for complete blood count were randomly selected and assayed for ESR. The reference interval (RI) was established using the percentile method. The coefficient of variation (CV) in intra-assay and interassay precision of ESR-MP was calculated. The analytical sensitivity (Se), specificity (Sp), positive predictive values (PPVs), and negative predictive values (NPVs) were calculated. Agreement between ESR-MP and ESR-W was assessed with Pearson correlation coefficient (r), Cohen concordance test (K), Passing-Bablok regression, and Bland–Altman plots. Ten canine samples (8.4%) were ruled out because of flag-error by the MINIPET instrument (4.2%) or because they showed the diphasic pattern in ESR-W (4.2%). The canine RI of ESR-MP was 0–10 mm/h. Precision was excellent in intra-assay (CV = 0.02) and interassay (CV = 0.32). The analytical characteristics of ESR-MP in nonanemic samples were as follows: Se = 0.82, Sp = 0.95, PPV = 0.82, and NPV = 0.95. The accuracy of ESR-MP was better than ESR-W in nonanemic samples (r = 0.87; K = 0.77) and lower in anemic subjects (Hct <37%) (r = 0.76; K = 0.69). The Passing-Bablok regression showed the presence of systematic error and the absence of proportional error only in nonanemic blood samples. The Bland–Altman plots gave negative average values due to the difference in RIs and an agreement in both ESRs. The ESR-MP results can be obtained with the same K3-EDTA tubes used for the blood count, in shortcut time, and at reduced costs using the MINIPET device. These investigations highlight that ESR-MP could be useful in canine clinical settings.